Fine Needle Aspiration Biopsy (FNAB) of masses from Thyroid and Salivary Glands: A Profile of 648 Cases (TAJ: Journal of Teachers Association, 2011)
DOI: http://dx.doi.org/10.3329/taj.v15i1.8375 TAJ 2002; 15(1): 17-21